Examining the Linkage between Poverty and Macroeconomic Variables in Malaysia: A Co-integration Analysis - Kaur, Gurmit; Jalil, Siti Ayu (Information Management and Business Review, 2017)
The purpose of this paper is to examine the linkage between the macroeconomic variables i.e. gross domestic product per capita (GDP), unemployment (UNE), tourist receipts (TOU), consumer price index (CPI) and poverty rate (POV) in Malaysia from 1969-2014. The econometric techniques used are unit root test and the Johansen Cointegration. The Granger Causality test using Block Exogeneity Wald test was added to analyze the causal relationships between the variables. The unit root test showed that all variables were stationary at first difference and thus the Johansen Co-integration test is an appropriate technique to employ. The evidence from co-integration test indicates that all the five series have three (3) co-integrating equations and significance at 1 percent level of significance. The causality test indicated there is a significant unidirectional causality between POV on GDP, CPI on POV, POV on TOU, GDP on UNE, GDP on TOU and CPI on TOU and bidirectional causality between POV and UNE. This paper is possibly the first to discuss these relationships in Malaysian context using Co-integration analysis. The finding implies that poverty is the key issue that should be addressed to achieve a high-income country status in the year 2020.